Modified cement system :durability and aesthetic - Siti Zarini Binti, Mohamed Jizi (Universiti Malaysia Sarawak (UNIMAS), 2009)
Efflorescence is a type of discoloration. It is a deposit salt, usually white in color that occasionally develops on the surface of concrete. Although unattractive, efflorescence is usually harmless to the structure such as concrete bridge. In rare cases excessive efflorescence, within the pores of the material, can cause expansion that may disrupt the surface. Efflorescence is caused when soluble salts and other water dispersible materials come to the surface of concrete and mortars. It is induced by low temperatures, moist conditions, condensation, rain, and water added to the surface of concrete. The modified cement system can reduce the efflorescence but cannot avoid it because of the reaction of cement hydration itself. This study proved that by using the modified cement system such as Pulverized Fly Ash (PFA) and Polymers (water based latex grade 29Y46), the efflorescence can be reduced. The mix proportion with and without PFA and Polymers are tested with various properties such as strength test, water absorption and efflorescence in order to understand the effect against the performance of the mortar. The results from this study showed that the modified mortar which is the sample with PFA and Polymers has higher strength, durability, and less efflorescence compared with non-modified cement system.